Enhanced Antidepressant-Like Effects of Electroacupuncture Combined with Citalopram in a Rat Model of Depression. (13th May 2013) - Yang, Jian; Pei, Yu; Pan, Yan-Li; Jia, Jun; Shi, Chen; Yu, Yan; Deng, Jia-Hui; Li, Bo; Gong, Xiao-Li; Wang, Xuan; Wang, Xiao-Min; Ma, Xin
Abstract : Currently, antidepressants are the dominative treatment for depression, but they have limitations in efficacy and may even produce troublesome side effects. Electroacupuncture (EA) has been reported to have therapeutic benefits in the treatment of depressive disorders. The present study was conducted to determine whether EA could enhance the antidepressant efficacy of a low dose of citalopram (an SSRI antidepressant) in the chronic unpredictable stress-induced depression model rats. Here, we show that a combined treatment with 2 Hz EA and 5 mg/kg citalopram for three weeks induces a significant improvement in depressive-like symptoms as detected by sucrose preference test, open field test, and forced swimming test, whereas these effects were not observed with either of the treatments alone. Further investigations revealed that 2 Hz EA plus 5 mg/kg citalopram produced a remarkably increased expression of BDNF and its receptor TrkB in the hippocampus compared with those measured in the vehicle group. Our findings suggest that EA combined with a low dose of citalopram could produce greater therapeutic effects, thereby, predictive of a reduction in drug side effects.